2017
DOI: 10.20960/nh.1085
|View full text |Cite
|
Sign up to set email alerts
|

Síndrome metabólico y grasa visceral en mujeres con un factor de riesgo cardiovascular

Abstract: ResumenIntroducción: las enfermedades cardiovasculares son la primera causa de muerte en las mujeres tras la menopausia, ya que después de esta etapa se producen profundos cambios metabólicos y hormonales que favorecen el desarrollo de síndrome metabólico. Un aumento en el porcentaje de la grasa visceral puede estar relacionado con la aparición de dicho síndrome. Objetivo: establecer la relación entre la grasa visceral y los parámetros del síndrome metabólico y determinar el punto de corte óptimo para las vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
(23 reference statements)
0
2
0
5
Order By: Relevance
“…Participants were not randomly assigned to the programmes, only the location of the flats were randomly assigned. Menopausal women showed more visceral fat [ 44 ], however we do not have this data. Manufacturers of BIA technology recommend to avoid testing women when they perceive to be retaining water during the menstrual cycle.…”
Section: Discussionmentioning
confidence: 98%
“…Participants were not randomly assigned to the programmes, only the location of the flats were randomly assigned. Menopausal women showed more visceral fat [ 44 ], however we do not have this data. Manufacturers of BIA technology recommend to avoid testing women when they perceive to be retaining water during the menstrual cycle.…”
Section: Discussionmentioning
confidence: 98%
“…называемые отрезные точки: их превышение свидетельствует о наличии у обследуемого метаболических нарушений [14][15]. По данным японского общества по проблемам ожирения под висцеральным ожирением понимают содержание висцеральной жировой ткани ≥ 10%.…”
Section: актуальная темаunclassified
“…8,9 Excessive visceral fat area is associated with adipocyte dysfunction, increased inflammatory cytokine secretion, and impaired insulin sensitivity, which can increase the risk of atherosclerosis and lead to cardiac and endothelial dysfunction. 10 A few studies reported visceral fat was associated with cardiometabolic risk in the general population, 11,12 in hypertensive patients, 13 in psoriasis patients, 14 in women after menopause 15 and in patients with coronary atherosclerosis. 16 However, the relationship between VFA and cardiac hemodynamics has not been adequately evaluated in comparison with other clinical factors such as blood pressure, age or waist/hip ratio in T2DM.…”
Section: Introductionmentioning
confidence: 99%